2011
DOI: 10.5144/1658-3876.2011.30
|View full text |Cite
|
Sign up to set email alerts
|

Age at transplantation and outcome after autologous stem cell transplantation in elderly patients with multiple myeloma

Abstract: BACKGROUND AND OBJECTIVE: The optimal treatment of patients with multiple myeloma (MM) is not well defined, in part because these patients are underrepresented in clinical studies. Autologous stem cell transplantation (auto-SCT) after high-dose melphalan chemotherapy can result in a prolonged response duration and survival in patients under 65 years of age. DESIGN AND SETTING: single-center, retrospective study of patients treated at Paoli-Calmettes Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 27 publications
4
23
2
2
Order By: Relevance
“…Several cohort studies, however, have compared the clinical outcomes for younger and older patients who underwent auto-HCT. In these studies, younger and older patients had similar response rates, progression-free survival (PFS)/time-to-progression (TTP), and overall survival (OS), 14,15,18,35 suggesting that auto-HCT may be a reasonable option for selected older adults with myeloma.…”
Section: Auto-hctmentioning
confidence: 88%
“…Several cohort studies, however, have compared the clinical outcomes for younger and older patients who underwent auto-HCT. In these studies, younger and older patients had similar response rates, progression-free survival (PFS)/time-to-progression (TTP), and overall survival (OS), 14,15,18,35 suggesting that auto-HCT may be a reasonable option for selected older adults with myeloma.…”
Section: Auto-hctmentioning
confidence: 88%
“…Reports show that this strategy has now become part of current clinical routine. 9,18,20,21,23 The proportion of patients receiving an ageadjustment of the melphalan dose is steadily increasing within the higher age groups when considering patients over the age of 60, over 65 and over 70 years. 9,20,21,23 If ageadjustment were to be applied consistently, many more older patients could be considered candidates for ASCT.…”
Section: Autotransplant With and Without Induction Chemotherapy In Olmentioning
confidence: 99%
“…These mostly report limited numbers of patients. [18][19][20][21][22][23] Registry data are lacking details of toxicity and outcome but demonstrate improvements in overall survival (OS) over the years. 8,9 Melphalan 200 mg/m 2 (MEL200) represents the standard high-dose regimen for the younger patient population.…”
Section: Autotransplant With and Without Induction Chemotherapy In Olmentioning
confidence: 99%
“…Based on these reports, elderly patients with MM in otherwise fit medical condition have been considered to be eligible for ASCT irrespective of the chronological age in many institutions [21,22]. Accordingly, several single institution studies have reported their experience of ASCT in elderly patients [23][24][25][26][27][28][29][30]. As conditioning regimen before ASCT, reduced dosing of melphalan (100-140mg/m2) has been predominantly used in elderly patients, with no significant difference in transplant-related mortality and morbidity between elderly and younger patients.…”
Section: Introductionmentioning
confidence: 99%